Dynamics Analysis of the Crank and Connecting Rod Mechanism with Clearance and Flexibility - Tingting Li; Zhenshan Zhang; Guohua Cui; Lianzhe Guan (Jixie chuandong)
Clearance joint and connecting rod flexibility are main factors that affect the dynamics performance of mechanism，which determine the reliability of mechanism operation. Crank and connecting rod mechanism as the object，the Lagrange multiplier method is used to establish the dynamics model of coupling connecting rod joint clearance and connecting rod flexible action. On this basis，the influence of clearance size，connecting rod flexibility and their coupling on the mechanism dynamics output response is systematically studied. The results show that，within the same cycle，the collisions are mainly concentrated in the early stage of the campaign close to the two sides of the crank，the connecting rod clearance increases，the collision between articulated components intensify，the oscillation amplitude of impact force and the embedding depth of increase obviously，and the stability of the axis trajectory is reduced，and the appropriate component flexible processing can reduce collisions caused by clearance joint.